COMPARISON OF PERINATAL OUTCOME IN GROWTH RESTRICTED FETUSES RETAINING NORMAL UMBILICAL ARTERY DOPPLER FLOW TO THOSE WITH DIMINISHED END-DIASTOLIC FLOW - Siddiqui, Tariq Saeed; Asim, Aisha; Ali, Shafqut; Siddiqui, Tahir Saeed; Tariq, Asima (Journal of Ayub Medical College Abbottabad, 2014)
Background Intrauterine growth restriction /retardation (IUGR) is defined as birth weight below the 10th percentile for a given gestational age. Placental insufficiency is the primary cause of intrauterine growth retardation in normally formed fetuses and can be identified using umbilical artery Doppler velocimetry which is a non-invasive technique. The objective of this study was to compare perinatal outcome in growth restricted fetuses retaining normal umbilical artery doppler flow to those with diminished or severely reduced/absent end-diastolic flow. Methods: This cross sectional study was conducted at Radiology department of Pakistan Navy Ship (PNS) Shifa Hospital, Karachi over one year period from. Established cases of asymmetrical IUGR, having estimated fetal weight <10th percentile for gestational age and between 28-40 weeks of gestation were included in the study. Pulsatility index (PI) was calculated for each case. Perinatal outcomes like early delivery, caesarean section, respiratory distress syndrome, necrotizing enterocolitis, admission to neonatal ICU, prenatal and neonatal death were evaluated. Chi-square test was used to compare proportion difference of perinatal outcomes for normal and abnormal umbilical artery velocimetry, with 0.05 level of significance. Results: Umbilical artery doppler velocimetry showed a significant correlation with the perinatal outcome. In 90% of cases of IUGR having abnormal waveform, poor perinatal outcome was seen as compared to only 33.3% retaining normal doppler flow. Conclusion: Growth restricted fetuses with normal umbilical artery doppler velocimetry were at lower risk than those with abnormal waveforms. Keywords: Umbilical artery Doppler; Intrauterine growth restriction; Perinatal outcome